Consumer Income and Beliefs Affecting Happiness - Prince, Mel; Manolis, Chris (Advances in Quality-of-Life Theory and Research, 2003)
Recent syntheses of empirical studies have clearly demonstrated a consistently positive relationship between income and happiness. Research is needed to reduce uncertainty and disentangle such relationships, which have been found to be quite modest, but significant in the aggregate. The present study contributes to this end, in that it investigates the moderating effect of income on the relationship between beliefs that serve as internal buffers and happiness. We go beyond simple associations of income and happiness to examine relationships between income and self-esteem and between income and optimism. Finally, causal modeling is employed to demonstrate that, under varying income levels, these beliefs affect happiness by the same process — with distinct yet predictable outcomes.
Citation Key Alias: lens.org/057-629-356-812-189, pop00235
Keywords: beliefs; causal model; dept.mkt; happiness; income; money

A model of job performance, job satisfaction, and life satisfaction among sales and sales support employees at a pharmaceutical company - Prince, Melvin; Engle, Robert L; Laird, Kenneth R (Journal of Pharmaceutical Marketing & Management, 2003)
This study investigates the influence of role conflict, role ambiguity, and role strain on job performance, job satisfaction, and life satisfaction among field sales and company sales support employees in a single pharmaceutical company. Because this study is based on data from a single company, these results may not necessarily be generalized to all companies in the industry. In the present research, a path model of the process reveals important variations in response to role conflict, role ambiguity, and role strain between the two classes of employees. For both classes, the influence of decreased role ambiguity is generally positive for measured outcomes. However, reductions in role conflict, while lessening role strain, are likely to result in lower job performance for field sales employees. Decreases in role strain, while improving life satisfaction, may lead to lower job satisfaction for sales support employees. © 2003, Informa UK Ltd All rights reserved: reproduction in whole or part not permitted. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-485-139-151-393 tex.type: [object Object]
Keywords: Job performance; dept.mkt; job satisfaction; life satisfaction; pharmaceutical sales; role strain

A marketing resource-based model of international market entry and expansion for professional services firms - Laird, Kenneth R; Kirsch, Robert J; Evans, Thomas G (Services Marketing Quarterly, 2003)
This paper examines the entry of the Big Six international accounting firms, into emerging foreign markets and explores marketing resource considerations once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. The paper presents a marketing resource-based model based upon relevant research. The model focuses on firm specific resource capabilities interacting with the foreign business environment and the foreign intrafirm structure as a determinant of foreign market entry choice and eventual market expansion. The research findings broaden our understanding of factors that influence professional services firms' development of marketing resource strategies when expanding globally. While all firms surveyed offered a full range of services, their marketing resource strategy differed from domestic approaches because of various local constraints on marketing mix elements. © 2003 Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-289-840-256-573 tex.type: [object Object]
Keywords: Commonwealth of Independent States; Eastern European and Baltic states; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt